He Has Shown You What is Good Old Testament Justice Then and Now. - Williamson, H. G. M. (Havertown : Lutterworth Press, 2012)
Can the Old Testament provide relevant principles for modern concepts of social justice? In this book, the author explores the meaning of Old Testament justice to discover its significance for us today. Concentrating on social justice he unearths the value and relevance of the phrase 'justice and righteousness'. Tracing this phrase and its context within and without the pages of Scripture Williamson elaborates an argument that passes from Abraham to Amos. He expounds a biblical ideal that he argues is not rooted in the legalistic Law of Moses, or necessarily an idealized history, but is a conc.
Hosea and MicahA wider survey of Amos; A wider survey of Isaiah; A new element; 5: Messianic Justice; Psalm 72; A developing hope; 6: He Has Shown You What is Good; Bibliography; Back-cover.
Print version record.
Master record variable field(s) change: 072
Keywords: Bible. -- Criticism, interpretation, etc; Bible; Justice -- Biblical teaching; Social justice -- Biblical teaching; BIBLES -- General; RELIGION -- Biblical Reference -- General; RELIGION -- Biblical Reference -- Handbooks; Justice -- Biblical teaching; Social justice -- Biblical teaching; RELIGION / Biblical Studies / Old Testament; Electronic books; Criticism, interpretation, etc